Modeling and Governance of the Country’s Energy Security: The Example of Ukraine - Yakymchuk, Alina; Kardash, Oksana; Popadynets, Nazariy; Yakubiv, Valentyna; Maksymiv, Yuliia; Hryhoruk, Iryna; Kotsko, Taras (International Journal of Energy Economics and Policy, 2022)
The research addresses the improvement of the methodology to evaluate the energy security through theoretical-methodological substantiation, development, and calculation of the integral index of its competitiveness for a country on the example of Ukraine. Establishing an efficient energy security (like a component of national security) system is a crucial issue in the current military-political situation in Ukraine. The global economic crisis and military aggression of the Russian Federation against Ukraine and the imposition of sanctions against it by European states have led to a deterioration in energy security of many energy-dependent EU countries. That is why the methodology of energy security calculations should be adapted to modern military-political instability conditions. The article aims to analyze active methods of state energy security in Ukraine and in the world. The authors’ methodology to calculate the integral index of energy security is suggested. Indicators of energy security include energy production, energy export, domestic consumption, capital investment in energy, etc. Every component of energy security will have factors of Russia’s war influence, which anyway in conclusion will correlate with the integral index of energy security. Integral indicators of energy security maintenance on the example of Ukraine.